The European Pillar of Social Rights: Impact and advancement. Somewhere between a compass and a steering tool - Björn Hacker (Stiftung Wissenschaft und Politik (SWP), 2023)
Social Europe is back on the political agenda - as a result of severe economic crises, prior austerity policies and a change in the European discourse framework. Six years after being announced, the European Pillar of Social Rights - although legally non-binding - has become the central reference point for social policy projects at the EU level. Slowly but steadily, the EU's social situation is improving, although major divergences remain. In the Member States, the Pillar and its accompanying Social Scoreboard are used only erratically. Social investments and reforms financed through the Recovery and Resilience Facility are only partly oriented towards social deficits. At the same time, European crisis management during the pandemic contributed to the implementation of the Pillar of Social Rights. This success was made possible by financially supported instruments such as the SURE short-time working scheme loans. The implementation of the Pillar could be stabilised through a series of measures. It would be advisable to use the indicators of the Scoreboard in a more targeted way at the national level, to develop SURE into a European unemployment insurance scheme, to set up a procedure on social imbalances and to create scope for social investments in the Stability and Growth Pact.
Keywords: 320; social rights; European Union (EU); economic crises; austerity policies; social situation; pandemic; SURE; Scoreboard; unemployment insurance; Stability and Growth Pact; welfare state